The content of resistin in the blood plasma and the activity of non-specific inflammation in patients with type 2 diabetes, depending on body weight and gender - Urbanovych, Alina (Journal of Education, Health and Sport, 2015)
Urbanovych Alina. Содержание резистина в плазме крови и активность неспецифического воспаления у больных сахарным диабетом 2 типа в зависимости от массы тела и пола = The content of resistin in the blood plasma and the activity of non-specific inflammation in patients with type 2 diabetes, depending on body weight and gender. Journal of Education, Health and Sport. 2015;5(11):68-77. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.33364 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A68-77 https://pbn.nauka.gov.pl/works/666653 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.09.2015. Revised 05.10.2015. Accepted: 30.10.2015. Содержание резистина в плазме крови и активность неспецифического воспаления у больных сахарным диабетом 2 типа в зависимости от массы тела и пола The content of resistin in the blood plasma and the activity of non-specific inflammation in patients with type 2 diabetes, depending on body weight and gender А. М. Урбанович Alina Urbanovych Львовский национальный медицинский университет имени Данила Галицкого, Украина Lviv National Medical University named Danylo Galyckyi Abstract Purpose of the research - to establish the correlation of resistin levels in blood plasma and markers of generalized non-specific inflammation in patients with diabetes type 2, depending on the presence of overweight and obesity, gender differences. Material and methods. The study involved 305 patients with diabetes type 2, which which were divided into three groups: group 1 with normal body weight - 43 patients, 2nd with overweight - 88 patients, 3rd with obesity - 174 patients. Were compared the level of resistin and tumor neсkrosis factor α (TNF-α), interleukin (IL)-2, IL-6 in these groups. Results. There were no significant differences in the content of resistin in the blood plasma of patients with type 2 depending on the presence of overweight and obesity. Revealed higher levels of TNF-a and IL-6 in patients of group 1 compared with patients of the 3rd group. During the correlation analysis was revealed a positive correlation of resistin levels with TNF-a and IL-2; insulin in overweight groups (r = 0,3881, p = 0,0004 and r= 0,2733, p = 0,0142; r = 0,2415, p = 0,0343) content resistin levels TNF-a and IL-2 group with obesity (r = 0,3255, p <0,2252 and r =0,0001, p = 0,0037), whereas in the group with normal weight is not detected correlation between resistin level with markers of generalized nonspecific inflammation and insulin levels. The difference in the content of resistin in the blood plasma of women and men, depending on body weight was not revealed. Conclusion. At type 2 diabetes is formed a new level of regulatory connections, where major role refers to the synthesis of cytokines, such as resistin, tumor neсkrosis factor α, interleukins. Key words: diabetes mellitus type 2, resistin, interleukin-2, interleukin-6, tumor neсkrosis factor α. Резюме Цель работы – установить взаимосвязь содержания резистина крови и маркеров генерализованного неспецифического воспаления у пациентов с СД 2-го типа в зависимости от наличия избыточного веса и ожирения, гендерних отличий. Материал и методы. Обследовано 305 пациентов с СД 2-го типа, которые были распределены на три группы: 1-я группа с нормальной массой тела - 43 пациента, 2-я с избыточной массой тела - 88 пациентов, 3-я с ожирением - 174 пациента. Сравнивали содержание резистина и туморнекротического фактора- α (TNF-α), интерлейкина (ИЛ)-2, ИЛ-6 в этих группах. Результаты. Не выявлено достоверной разницы в содержании резистина в плазме крови пациентов с СД 2 в зависимости от наличия избыточного веса и ожирения. Выявлено более высокие уровни TNF-a и ИЛ-6 у пациентов 1-й группы по сравнению с пациентами 3-й группы. При проведении корреляционного анализа выявлена положительная корреляция содержания резистина с уровнями TNF-a и ИЛ-2; инсулина в группах с избыточным весом (r = 0,3881, p = 0,0004 и r = 0,2733, p = 0,0142; r = 0,2415, р = 0,0343) содержания резистина с уровнями TNF-a и ИЛ-2 в группе с ожирением (r = 0,3255, p <0,0001та r = 0,2252, p = 0,0037), тогда как в группе с нормальным весом не обнаружено корреляции уровня резистина с маркерами генерализованного неспецифического воспаления и уровнем инсулина. Не установлено разницы в содержании резистина в плазме крови у женщин и мужчин в зависимости от массы тела. Заключение. При СД 2 типа формируется новый уровень регуляторных взаимосвязей, где важное значение имеют изменения в синтезе цитокинов, в частности резистина, туморнекротического фактора α, интерлейкинов. Ключевые слова: сахарный диабет 2 тип, резистин, интерлейкин-2, интерлейкин-6, туморнекротический фактор α.